2015
DOI: 10.1007/s13277-015-3874-4
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent effects of ABCB1 C3435T, ABCG2 C421A, and XRCC1 Arg194Trp genetic polymorphisms with risk of cancer, clinical output, and response to treatment with imatinib mesylate in patients with chronic myeloid leukemia

Abstract: There are a paucity and contradicted data about the impact of concurrent heredity of polymorphic genes and risk of chronic myeloid leukemia (CML). In the present study, the concurrent effects of three polymorphisms affecting the integrity of DNA consist of ABCB1 C3435T, ABCG2 C421A, and XRCC1 Arg194Trp on development of chronic myeloid leukemia were studied. Furthermore, the role of these polymorphisms in clinical and laboratory outcomes of patients was evaluated. In this case-control study, 70 CML patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 50 publications
2
15
2
4
Order By: Relevance
“…Studies conducted on Malaysian CML patients had shown no relationship between 3435C>T polymorphism and response to a standard dose of IM 89. In a recent study by Salimizand et al,90 CML patients with C allele of ABCB1 C3435T had poor cytogenetic response and TT3435 ABCB1 diplotype was significantly associated with accelerated phase of CML. This study also indicated that CML patients with TT3435 ABCB1 might be having weaker response to IM therapy.…”
Section: Abcb1 Variants and CML Treatmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies conducted on Malaysian CML patients had shown no relationship between 3435C>T polymorphism and response to a standard dose of IM 89. In a recent study by Salimizand et al,90 CML patients with C allele of ABCB1 C3435T had poor cytogenetic response and TT3435 ABCB1 diplotype was significantly associated with accelerated phase of CML. This study also indicated that CML patients with TT3435 ABCB1 might be having weaker response to IM therapy.…”
Section: Abcb1 Variants and CML Treatmentmentioning
confidence: 96%
“…It has been reported90 that the ABCB1 2677 G>T/A single nucleotide substitution strongly affects the secondary structure of ABCB1 mRNA. A decrease in P-gp expression could result in higher intracellular concentration of IM.…”
Section: Abcb1 Variants and CML Treatmentmentioning
confidence: 99%
“…In the present study, we analyzed the effects of the C3435T and G2677T/A polymorphisms in the ABCB1 gene on the risk of developing bullous pemphigoid (BP) in a Polish population. Available data suggests that genetically determined P‐gp polymorphisms may predispose to the development of neoplasms, neurological disorders, and diseases of the gastrointestinal tract .…”
Section: Discussionmentioning
confidence: 99%
“…1 Krasnoyarsk branch of the «National Research Center for Hematology» Department of Health, Krasnoyarsk, Russia; 2 Federal Research Center Krasnoyarsk Scientific Center, Siberian Branch of RAS, Krasnoyarsk, Russia; 3 Krasnoyarsk City Clinical Hospital №7, Krasnoyarsk, Russia; 4 Regional Clinical Hospital, Krasnoyarsk, Russia; 5 Siberian Federal University, Krasnoyarsk, Russia…”
Section: A Study Of the Association Of C3435t Polymorphism Of Mdr1 Gementioning
confidence: 99%